2012
DOI: 10.1017/s1355617712000239
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Outcome from Blast versus Non-blast: Mild Traumatic Brain Injury in U.S. Military Service Members

Abstract: The purpose of this study was to compare the neuropsychological outcome from blast-related versus non-blast related mild traumatic brain injury (MTBI). Participants were 56 U.S. military service members who sustained an MTBI, divided into two groups based on mechanism of injury: (a) non-blast related (Non-blast; n 5 21), and (b) blast plus secondary blunt trauma (Blast Plus; n 5 35). All participants had sustained their injury in theatre whilst deployed during Operation Iraqi Freedom or Operation Enduring Free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 34 publications
1
24
1
1
Order By: Relevance
“…No previous studies specifically investigated the association between TBI blast mechanism and persistent symptom resolution; however, our finding is in contrast with other studies that explored the association between initial persistent symptom burden and blast mechanism and have found no significant difference. [58][59][60][61] Thus, future studies are warranted to establish the true association between blast mechanism and persistent symptom resolution.…”
Section: Discussionmentioning
confidence: 99%
“…No previous studies specifically investigated the association between TBI blast mechanism and persistent symptom resolution; however, our finding is in contrast with other studies that explored the association between initial persistent symptom burden and blast mechanism and have found no significant difference. [58][59][60][61] Thus, future studies are warranted to establish the true association between blast mechanism and persistent symptom resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, some authors have identified quaternary bTBI effects due to other damaging elements associated with the nature of the explosive device used, such as radiation, heat, or the release of chemicals (DeWitt and Prough, 2009). In selecting “blast-injured” TBI subjects for investigations, it is typical to include those with secondary and tertiary effects of blast (sometimes referred to as “blast-plus,” i.e., Moore and Jaffee, 2010; Lange et al, 2012). This is largely due to the rarity of documented isolated primary blast in this population.…”
Section: Blast-related Brain Injury Mechanismsmentioning
confidence: 99%
“…Although differences in injury characteristics likely exist, there are also likely important areas of overlap between blast and non-blast injury mechanisms, injury sequelae, and associated research findings. Certainly from a neurocognitive standpoint, no differences have been found in neuropsychological evaluations between groups of service members sustaining TBI through a blast-related mechanism versus another mechanism (Belanger et al, 2009; Lange et al, 2012). …”
Section: Relevance Of Non-blast Tbi Findings To Blast-related Tbimentioning
confidence: 99%
“…Currently, it is widely accepted that blast exposure poses a risk to the central nervous system (CNS) of Service Members (SM), though there remains much to be learned about the severity and functional impact. For this reason, blast injury remains a primary focus of many research endeavors across the spectrum of clinical, mechanical, and neuropathology research (Brenner et al 2012; Goeller et al 2012; Lange et al 2012; Panzer et al 2012). …”
Section: Introductionmentioning
confidence: 99%